Cell Cycle-Dependent Binding of Yeast Heat Shock Factor to Nucleosomes - Venturi, Christina Bourgeois (American Society for Microbiology, 2000)
In the nucleus, transcription factors must contend with the presence of chromatin in order to gain access to their cognate regulatory sequences. As most nuclear DNA is assembled into nucleosomes, activators must either invade a stable, preassembled nucleosome or preempt the formation of nucleosomes on newly replicated DNA, which is transiently free of histones. We have investigated the mechanism by which heat shock factor (HSF) binds to target nucleosomal heat shock elements (HSEs), using as our model a dinucleosomal heat shock promoter (hsp82-ΔHSE1). We find that activated HSF cannot bind a stable, sequence-positioned nucleosome in G(1)-arrested cells. It can do so readily, however, following release from G(1) arrest or after the imposition of either an early S- or late G(2)-phase arrest. Surprisingly, despite the S-phase requirement, HSF nucleosomal binding activity is restored in the absence of hsp82 replication. These results contrast with the prevailing paradigm for activator-nucleosome interactions and implicate a nonreplicative, S-phase-specific event as a prerequisite for HSF binding to nucleosomal sites in vivo.